2013
DOI: 10.1057/jphp.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

Cellphone bans and fatal motor vehicle crash rates in the United States

Abstract: A number of states in the United States have laws restricting drivers from using cellphones. Using state-level panel data, we examined the effect of cellphone laws on fatal crashes in the United States between 2000 and 2010. Our results show that there is insufficient power to detect a reduction in overall fatal crash rates scaled by vehicle miles and population estimates. Cellphone bans, however, have significantly reduced the fatal crash rates of drivers in certain age cohorts. The effect was most pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
3
17
0
Order By: Relevance
“…In this analysis, UHB were associated with 10% lower driver fatalities overall. This was comparable to other studies which have shown that UHB were associated with 7–13% lower fatalities for all drivers [13, 14, 19, 21]. As for specific age groups, in this analysis driver fatalities were 14% lower for 16–39 year olds, 11% lower for 40–59 year olds, and 8% lower for drivers ≥60 years of age when UHB were effective compared to when they were not.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this analysis, UHB were associated with 10% lower driver fatalities overall. This was comparable to other studies which have shown that UHB were associated with 7–13% lower fatalities for all drivers [13, 14, 19, 21]. As for specific age groups, in this analysis driver fatalities were 14% lower for 16–39 year olds, 11% lower for 40–59 year olds, and 8% lower for drivers ≥60 years of age when UHB were effective compared to when they were not.…”
Section: Discussionsupporting
confidence: 87%
“…As for specific age groups, in this analysis driver fatalities were 14% lower for 16–39 year olds, 11% lower for 40–59 year olds, and 8% lower for drivers ≥60 years of age when UHB were effective compared to when they were not. Other studies have similarly reported that UHB were associated with 6–9% lower fatalities amongst 18–54 year old drivers [19], ~8% less for drivers <21 years [18], and 4% less for drivers aged 22–64 years [16]. However, the findings concerning UTB were akin to some studies and dissimilar from others.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…While pedestrian deaths due to distracted driving are reportedly on the rise, we were unable to test this in our population because driver distraction was not consistently reported (Stimpson et al, 2013;Wilson and Stimpson, 2010). Perhaps prevention efforts designed to decrease distracted driving are working to suppress a rise in pedestrian crashes overall as seen in other studies (McCartt et al, 2014;Lim and Chi, 2013). 1,2,3 Declining incidence over time may also reflect diminishing outdoor activity time in children and adolescents as suggested by other studies (Clements, 2004;Hofferth and Sandberg, 2001).…”
Section: Pedestrian Injury Trends Over Timementioning
confidence: 79%
“…The most notable of these regulations included the 2005 Chicago ban on handheld cellphone devices while driving, the 2008 Chicago texting while driving ban, and the 2010 Illinois state-wide texting while driving ban. 1,2,3 However, studies have shown varying efficacy of similar policies in other locals (McCartt et al, 2014;Lim and Chi, 2013). …”
Section: Influence Of Traffic Technology Changes Personal Electronicmentioning
confidence: 99%